Prevention and Treatment of Intestinal Failure-Associated Liver Disease in Children - Lorenzo Norsa (Nutrients, 2018)
Intestinal failure-associated liver disease (IFALD) is a threatening complication for children on long-term parenteral nutrition because of intestinal failure. When progressive and intractable, it may jeopardize intestinal rehabilitation and lead to combined liver and intestinal transplantation. The institution of dedicated intestinal failure centers has dramatically decreased the incidence of such complication. IFALD may rapidly fade away if very early management aimed at preventing progression to end-stage liver disease is provided. In this review, we address the etiology and risk factors of IFALD in order to introduce pillars of prevention (nutritional management and catheter-related infections control). The latest evidence of therapeutic strategies, such as medical and surgical treatments, is also discussed.